Cervical Gene Delivery of the Antimicrobial Peptide, Human β-Defensin (HBD)-3, in a Mouse Model of Ascending Infection-Related Preterm Birth - Suff, Natalie; Karda, Rajvinder; Diaz, Juan Antinao; Ng, Joanne; Baruteau, Julien; Perocheau, Dany; Taylor, Peter W.; Alber, Dagmar; Buckley, Suzanne M. K.; Bajaj-Elliott, Mona; Waddington, Simon N.; Peebles, Donald (Frontiers in Immunology, 2020)
Approximately 40% of preterm births are preceded by microbial invasion of the intrauterine space; ascent from the vagina being the most common pathway. Within the cervical canal, antimicrobial peptides and proteins (AMPs) are important components of the cervical barrier which help to prevent ascending vaginal infection. We investigated whether expression of the AMP, human β-defensin-3 (HBD3), in the cervical mucosa of pregnant mice could prevent bacterial ascent from the vagina into the uterine cavity. An adeno-associated virus vector containing both the HBD3 gene and GFP transgene (AAV8 HBD3.GFP) or control AAV8 GFP, was administered intravaginally into E13.5 pregnant mice. Ascending infection was induced at E16.5 using bioluminescent E.coli (E.coli K1 A192PP-lux2). Bioluminescence imaging showed bacterial ascent into the uterine cavity, inflammatory events that led to premature delivery and a reduction in pups born alive, compared with uninfected controls. Interestingly, a significant reduction in uterine bioluminescence in the AAV8 HBD3.GFP-treated mice was observed 24 hours post-E.coli infection, compared to AAV8 GFP treated mice, signifying reduced bacterial ascent in AAV8 HBD3.GFP-treated mice. Furthermore, there was a significant increase in the number of living pups in AAV HBD3.GFP-treated mice. We propose that HBD3 may be a potential candidate for augmenting cervical innate immunity to prevent ascending infection-related preterm birth and its associated neonatal consequences.